Correlation of Cardiotocography with Intraoperative findings and neonatal outcome in caesarean section for non-reassuring fetal status - Singh, Arju Chand; Khatri, Ratna; Chauhan, Pradyuman; Thapa, Sumana (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To demonstrate the correlation of cardiotocography with intraoperative findings and neonatal outcome undergoing emergency cesarean section for non-reassuring fetal status. Methods: It is a hospital based cross sectional study at maternity ward of Shree Birendra Hospital in Kathmandu with non-reassuring CTG who underwent cesarean section in a period of one year. Their CTG were correlated with their intraoperative findings and neonatal outcome such as meconium stained liquor, nuchal cord, Apgar score at birth, NICU admission, perinatal mortality and stillbirth. Results: Fifty four patients were recruited. Most common operative finding was meconium stained liquor (35.2%); and cardiotocographic abnormality was variable Deceleration (37%). Variable deceleration and late deceleration had significant correlation with meconium stain liquor and nuchal cord. Apgar score ≤ 7 at 5 minute was 7.4%. NICU admission was 13% with common abnormality as late Deceleration. Conclusion: CTG pattern of variable and late deceleration had correlated with the meconium stained liquor and nuchal cord only. There was no relation with neonatal outcome in terms of Apgar score and admission rate.